Analysis of Teaching Material Delivery Techniques by Lecturers Based on E-Learning at Universitas Pembangunan Panca Budi Medan - Fauziah, Fauziah; Mutia, Cut; Meiditra, Irzon; Yuda, Fitra; Rahmansyah, Rizky (Internet of Things and Artificial Intelligence Journal, 2025)
The rapid development of technology has also affected the world of education, both in terms of facilities, infrastructure, and learning methods. Schools and universities now utilize technology to support the teaching and learning process, making it more efficient, interesting, and accessible. Technology acts as a means, media, and learning resources that help facilitate learning between educators and students. One form of technology application in education is the use of videos and E-Learning-based learning portals. At Universitas Pembangunan Panca Budi, the E-Learning system continues to be developed in terms of features, security, and interface to support effective distance learning between students and lecturers.